2014
DOI: 10.1111/ijcp.12448
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones in clinical practice: reducing the risk of bacterial contamination

Abstract: Summary Background Mobile smart phones have become increasingly integrated into the practice of doctors and allied medical professionals. Recent studies suggest them to represent reservoirs for pathogens with potential to cause nosocomial infections. This study aimed to investigate the level of contamination on phones used on surgical wards and identify strategies for their safe use within clinical areas. Methods Fifty mobile phones were taken from members of the multidisciplinary team working in a surgical un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 12 publications
5
38
0
1
Order By: Relevance
“…Studies have reported that between 85% and 93% of HCWs never clean their MCDs (Singh et al, 2002;Hassoun et al, 2004;Brady et al, 2007). Furthermore, Mark et al (2014) found that 45% of medical professionals never wash their hands after phone usage. Since a significant number of MCDs carry pathogenic bacteria, there is a need to determine the risk of transmission from MDCs to both HCWs and patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have reported that between 85% and 93% of HCWs never clean their MCDs (Singh et al, 2002;Hassoun et al, 2004;Brady et al, 2007). Furthermore, Mark et al (2014) found that 45% of medical professionals never wash their hands after phone usage. Since a significant number of MCDs carry pathogenic bacteria, there is a need to determine the risk of transmission from MDCs to both HCWs and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, healthcare workers (HCWs) use MCDs on a day-to-day basis for work and social purposes. Studies indicate that 87%Á88% of HCWs use their MCD at the workplace (Koehler et al, 2013;Mark et al, 2014). These devices are used primarily to optimize patient care and client communications ( Julian et al, 2012).…”
Section: Mobile Communication Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sob a maioria das condições não é biologicamente ativo e está presente sob a forma de esporos. 17 As taxas de infecção relacionadas a assistência à saúde continuam sendo uma preocupação crescente para profissionais de saúde. Diversas orientações têm sido dadas em relação à limpeza das mãos, descontaminação de superfícies, e limpeza de instrumentos utilizados AVALIAÇÃO …”
Section: -14unclassified